2011
DOI: 10.1007/s10664-011-9180-x
|View full text |Cite
|
Sign up to set email alerts
|

Time variance and defect prediction in software projects

Abstract: It is crucial for a software manager to know whether or not one can rely on a bug prediction model. A wrong prediction of the number or the location of future bugs can lead to problems in the achievement of a project's goals. In this paper we first verify the existence of variability in a bug prediction model's accuracy over time both visually and statistically. Furthermore, we explore the reasons for such a high variability over time, which includes periods of stability and variability of prediction quality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…This confirms previous findings by Ekanayake et al [52] on the variability of the change-proneness of classes during different stages of software evolution. As a consequence, the previous knowledge about the number of changes a class underwent is not always suitable to correctly identify change-prone classes in future versions of a software system.…”
Section: B Rq 2 : the Comparison Between Developer-based And State-osupporting
confidence: 92%
“…This confirms previous findings by Ekanayake et al [52] on the variability of the change-proneness of classes during different stages of software evolution. As a consequence, the previous knowledge about the number of changes a class underwent is not always suitable to correctly identify change-prone classes in future versions of a software system.…”
Section: B Rq 2 : the Comparison Between Developer-based And State-osupporting
confidence: 92%
“…By studying four open source systems, Ekanayake et al [11] investigated the notion of concept drift and its impact on defect prediction. Further study by Ekanayake et al [18] revealed that the number of authors editing software projects contributes to concept drift and results in fluctuating software quality.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Amongst the common challenges of software defect datasets tackled in literature are class imbalance [15], [16] and feature selection [17]. Ekanayake et al [18] observed that the prediction quality of models for software projects changes over time as the number of developers editing and fixing defects on the files changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it does not necessarily indicate the importance that each topic has in CR management. Additionally, the studies [12,18,22,24,56,81,83,88,91,117,121,122,123,124] [ 69,70,71,72,73,74,75,76 ] that addressed more than one topic were classified repeatedly in each topic, that is, since Hosseini et al [19] investigated the topics of CR assignment and time to fix, their study is counted under both two topics.…”
Section: Classification Schemementioning
confidence: 99%